Accurate parametrization revealing an extremely low disorder in polymer field-effect transistors. (1st June 2022) - Romanjek, Krunoslav; Charbonneau, Micaël; Kim, Chang-Hyun
Abstract: In this paper, a robust self-consistent parameter extraction method is applied to high-performance p -type printed polymer field-effect transistors. Simultaneous extraction of contact resistance and intrinsic channel mobility with their full gate-voltage dependence is achieved through an analytically reinforced transmission-line method. The proposed method yields a minimum width-normalized contact resistance of 12 kΩ cm and a maximum hole mobility of 1.9 cm 2 V −1 s −1 . Moreover, the gate-voltage-dependent mobility is interpreted in the framework of trap-and-release transport through double-exponential density of states, unveiling a disorder energy near the transport orbital as low as 29 meV.